Connotation, layering, mapping and supporting objectives of the integrated survey of ground substrates - Zhiqiang YIN; Ziran CHEN; Xia LI; Xiaofeng WEI; Hai SHAO (Shuiwen dizhi gongcheng dizhi, 2023)
Comprehensive investigation and evaluation of ground substrate is the fundamental work to support suitable forest, grass, farming and wasteland. The guiding theory, target positioning, scientific connotation and mapping unit of comprehensive investigation of ground substrate are the focus and hotspot of current scientific issues. In this paper, based on the comprehensive survey and multi-scale mapping of ground substrate in Chengde Ecological Civilization Demonstration Area in recent years, and combined with the pilot practices of ground substrate survey in different regions, we further clarify the scientific connotation and supporting service objectives of ground substrate, establish the fourth-level classification scheme, mapping unit and naming convention, and proposed the depths range of the production layer, ecological layer and living layer of ground substrate. Finally we take two cases of afforestation and grass degeneration in the Bashang region as examples to reveal the constraining effect of ground substrate on vegetation community. All the above research results will provide a fundamental reference for understanding in-depth of the scientific significance of ground substrate and implementation of survey, monitoring, evaluation and zoning of ground substrate in China.